Innovative Reading Aloud Approach for Enhancing Pronunciation and Speaking Fluency of Students - Dwi Latifatul Aini; Kristianti Sukmawati; Tri Wahyudi Amroni (Ihsan Cahaya Pustaka, 2025)
Pronunciation is a vital component of English language mastery, yet many EFL learners face persistent challenges due to limited exposure and practice. This study examines the effectiveness of an innovative Reading Aloud approach in enhancing pronunciation and speaking fluency among students. The approach integrates structured phonetic drills, prosodic awareness training, and peer feedback within a communicative learning framework. Using a pre-experimental design with a single-group pretest–posttest, participants were assessed through targeted pronunciation tests focusing on the /ʃ/, /ð/, and /θ/ sounds. Data were analyzed using the Wilcoxon signed-rank test to measure improvement. Findings reveal a significant enhancement in pronunciation accuracy (p = 0.0367 < 0.05; Z = –2.089), with most participants demonstrating notable progress. Students also reported increased confidence and motivation in oral communication. The novelty of this study lies in combining traditional reading aloud with interactive, feedback-driven activities to address specific phoneme articulation issues in the school context. These results underscore the potential of the Reading Aloud approach as an effective, low-cost, and adaptable technique for EFL pronunciation teaching. Future studies should expand the sample size and compare its effectiveness with other pronunciation-focused instructional strategies.